2016
DOI: 10.1515/ijek-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Most Important Attributes of Entrepreneurs. Case Study of the Environment of Czech SMEs.

Abstract: The aim of this paper was to define and quantify the most important attributes of entrepreneurs in the segment of small and medium-sized enterprises. The partial objective was to compare the opinions of the entrepreneurs in relation to their gender, age and level of education. Scientific questions, defined in this paper, were verified through empirical research conducted in the Czech Republic in 2015 on a sample of 1,141 entrepreneurs. In our research, we found that entrepreneurs consider expertise, responsibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Entrepreneurs ought to acknowledge difficulties and indeed be willing to begin from scratch in order to achieve their business goals. Belás and Ključnikov, in their study, concluded that "entrepreneurs consider expertise, responsibility and perseverance to be the most important personal characteristics and skills" (Belás and Ključnikov, 2016). This indicates that students who enjoy perseverance characteristic may be more inclined to establish their own business.…”
Section: Perseverancementioning
confidence: 98%
“…Entrepreneurs ought to acknowledge difficulties and indeed be willing to begin from scratch in order to achieve their business goals. Belás and Ključnikov, in their study, concluded that "entrepreneurs consider expertise, responsibility and perseverance to be the most important personal characteristics and skills" (Belás and Ključnikov, 2016). This indicates that students who enjoy perseverance characteristic may be more inclined to establish their own business.…”
Section: Perseverancementioning
confidence: 98%
“…Scholars are trying to identify the contributing risk factors of student's entrepreneurial intention for their future career. The willingness in becoming entrepreneurship are determined by some other factors such as family, motivation, risk taking propensity or the courage to take a risk, and self-concept as individual factor [4,21,44]. Family environment and all conditions within its family including how parents educate, family member's relation, house condition, family's financial condition, parents understanding, and cultural background will support, guide, and encourage children to their future life.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the competency approach has become popular to study the entrepreneur's characteristics (Belás and Ključnikov, 2016;Chatterjee and Das, 2016;Kyndt and Baert, 2015;Lans et al, 2005;Xiang, 2009;Manzanera-Román and Brändle, 2016), but literature on rural tourism is scarce. In small rural tourism lodging establishments a combination of inherited or created assets and processes influence success.…”
Section: Table 1 Functional Competencies Of Entrepreneurial and Perso...mentioning
confidence: 99%